Effect of nose twitching on the pupillary dilation in awake and anesthetized horses - Mascaró Triedo, Carlota Emilia; Karar, Sahra; Abunemeh, Maha; Portier, Karine (Frontiers in Veterinary Science, 2024)
Pupillometry is used in humans to monitor pain, nociception and analgesia. This single-center, non-randomized, non-blinded intervention trial, evaluated the effect of nose twitching on the pupil size in awake, sedated, and anesthetized horses. Pupil height (H) and length (L) were measured before (Be) and after (Af) nose twitching in fourteen non-painful adult awake horses (T0). The percentage of variation (PSV) was calculated (PSVTn = [(TnAf-TnBe)/TnBe]*100). Measurements were repeated (Tn) after acepromazine (0.04 mg kg−1 IV) (T1), romifidine (0.04 mg kg−1 IV) (T2), morphine (0.1 mg kg−1 IV) (T3), after anesthesia induction with diazepam (0.05 mg kg−1 IV) and ketamine (2.2 mg kg−1 IV), at the time the horse was placed on the operating table (T4) and when the expiratory fraction of sevoflurane was 2% (T5). HAf vs. HBe, LAf vs. LBe as well as PSVH vs. PSVL at each time were compared with a Mann–Whitney Wilcoxon test. The PSVL and PSVH, as well as HBe and LBe over time were compared with the Skillings-Mack test followed by a Wilcoxon test for paired data to make pairwise comparisons (Tn + 1 vs. Tn). In non-sedated horses (T0), the application of the nose twitch induced a significant increase in pupil length (LT0Be: 17.09 [16.05; 19.67] mm versus LT0Af: 19.52 [18.74; 21.40]) mm (p = 0.004). Thirty minutes after acepromazine administration (T1), nose twitching induced a significant increase in pupil length (LT1Be: 16.45 [14.80; 18.66] mm versus LT1Af 18.31 [17.20; 20.52] mm) (p = 0.016) and height (HT1Be: 8.44 [5.68; 12.04] mm versus HT1Af: 11.09 [7.97; 14.3] mm) (p < 0.001). PSVHT1 was significantly greater than PSVLT1 (p = 0.025). PSVH was higher at T1 than at T0 (p = 0.04). It was also significantly higher at T1 than at T2 (p < 0.001). Romifidine induced mydriasis (HT2Be 16.95 [14.73; 18.77] mm versus HT1Be 8.44 [5.68; 12.04] mm) (p < 0,001) (LT2Be 19.66 [18.45; 20.41] mm versus LT1Be 16.45 [14.80; 18.66] mm) (p < 0.001). The results suggest that nose twitching induced a pupillary dilation in the awake horse. This effect was potentiated after the administration of acepromazine but disappeared after the administration of romifidine.